2021
DOI: 10.3390/v13061062
|View full text |Cite
|
Sign up to set email alerts
|

The Pro-Inflammatory Chemokines CXCL9, CXCL10 and CXCL11 Are Upregulated Following SARS-CoV-2 Infection in an AKT-Dependent Manner

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a highly transmissible RNA virus that is the causative agent of the Coronavirus disease 2019 (COVID-19) pandemic. Patients with severe COVID-19 may develop acute lung injury (ALI) or acute respiratory distress syndrome (ARDS) and require mechanical ventilation. Key features of SARS-CoV-2 induced pulmonary complications include an overexpression of pro-inflammatory chemokines and cytokines that contribute to a ‘cytokine storm.’ In the current study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
65
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 59 publications
(92 reference statements)
9
65
1
1
Order By: Relevance
“…Multiple studies reported the massive and dysregulated production of inflammatory cytokines and growth factors in patients with severe COVID-19. In line with previous reports, we detected the production of inflammatory cytokines and growth factors in SARS-CoV-2-infected Calu-3 epithelial lung cells (Callahan et al, 2021;Islam et al, 2021). Of note, key inflammatory factors and drivers of COVID-19-induced cytokine storm were included in our analysis (IL-6, IL-8, IL-13, TNF-α, CXCL9, CXCL10, PDGF, VEGF-A, CD40L, IL1RA) and showed robust upregulation in infected Calu-3 cells (see Figure 6 for graphical overview and details) (Cauchois et al, 2020;Donlan et al, 2021;Pang et al, 2021;Petrey et al, 2021;Sugiyama et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Multiple studies reported the massive and dysregulated production of inflammatory cytokines and growth factors in patients with severe COVID-19. In line with previous reports, we detected the production of inflammatory cytokines and growth factors in SARS-CoV-2-infected Calu-3 epithelial lung cells (Callahan et al, 2021;Islam et al, 2021). Of note, key inflammatory factors and drivers of COVID-19-induced cytokine storm were included in our analysis (IL-6, IL-8, IL-13, TNF-α, CXCL9, CXCL10, PDGF, VEGF-A, CD40L, IL1RA) and showed robust upregulation in infected Calu-3 cells (see Figure 6 for graphical overview and details) (Cauchois et al, 2020;Donlan et al, 2021;Pang et al, 2021;Petrey et al, 2021;Sugiyama et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Both viral components activated NF-kappaB and induced the expression of the pro-inflammatory chemokine CXCL10. An increase in CXCL10 has previously been reported in Calu-3 lung epithelial cells in mice lungs following SARS-CoV-2 infection 26 and in COVID-19 patients 27 , implicating this chemokine as a key contributor to SARS-CoV-2-related cytokine storm. In our experimental model the IFN-γ response was of limited magnitude; however, in an in vitro study, Yeruva et al .…”
Section: Discussionmentioning
confidence: 67%
“…MMP-9 can cleave various proteins to regulate inflammation and injury responses ( Bradley et al, 2012 ). MMP-9 can mediate the migration of neutrophils into the airway in response to Toll-like receptor signals induced by influenza viruses ( Callahan et al, 2021 ). The main characteristics of SARS-CoV-2 induced pulmonary complications include the overexpression of pro-inflammatory chemokines and cytokines, which can lead to a “cytokine storm.” After SARS-CoV-2 infects Calu-3 human lung epithelial cells, the pro-inflammatory chemokines CXCL9, CXCL10, and CXCL11 are up-regulated in an AKT-dependent manner ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%